CALR, JAK2 and MPL mutation status in Argentinean patients with BCR-ABL1- negative myeloproliferative neoplasms - Ojeda, Mara Jorgelina (2017)
Fil: Fil: Ojeda, Mara Jorgelina. Universidad Nacional de Rosario. Facultad de Ciencias Bioquímicas y Farmacéuticas. Cátedra de Hematología; Argentina.